2018
DOI: 10.1149/2.1291810jes
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable and Methanol Tolerant RuTe2/C Electrocatalysts for Fuel Cell Applications

Abstract: Carbon supported ruthenium tellurium (RuTe 2 /C) catalysts were synthesized with various Ru/Te ratios ( 2:1, 1.5:1, 1:1, 1:2, and 1:3) via a microwave route followed by heat-treatment. Effects of Ru/Te ratio on crystal structures, microstructures, chemical states and electrocatalytic activities toward oxygen reduction reaction (ORR) of RuTe 2 /C were systematically investigated. A mixed phase with predominant orthorhombic RuTe 2 and minor hexagonal Ru was identified. A novel synergistic effect was provided by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
3
5
0
Order By: Relevance
“…The recorded XRD data were matched and indexed with patterns for the pure compounds extracted from the powder diffraction database by the International Centre for Diffraction Data (ICDD). The patterns generally showed a good match to the theoretical reflections as well as data in the literature and no evidence of impurity phases, with the exception of an unidentified peak at 24°, 2θ, for ReSe 2 . The pattern of ReTe 2 deviated from the crystallographic data for the polymorphs reported in the literature, but no obvious signs of impurities, such as the initial elemental reagents and their respective oxides, were found. It is possible that a new polymorph of ReTe 2 was made in these conditions . This possibility will be further explored in follow-up reports.…”
Section: Resultssupporting
confidence: 56%
“…The recorded XRD data were matched and indexed with patterns for the pure compounds extracted from the powder diffraction database by the International Centre for Diffraction Data (ICDD). The patterns generally showed a good match to the theoretical reflections as well as data in the literature and no evidence of impurity phases, with the exception of an unidentified peak at 24°, 2θ, for ReSe 2 . The pattern of ReTe 2 deviated from the crystallographic data for the polymorphs reported in the literature, but no obvious signs of impurities, such as the initial elemental reagents and their respective oxides, were found. It is possible that a new polymorph of ReTe 2 was made in these conditions . This possibility will be further explored in follow-up reports.…”
Section: Resultssupporting
confidence: 56%
“…For different RuSe 2 /C catalysts, the half-wave potential ( E 1/2 ) varied from 0.65 to 0.71 V, with the onset potential ( E onset ) ranging from 0.91 to 0.92 V in HClO 4 solutions. RuSe 2 /C (Se/Ru = 2.5) exhibited the largest E 1/2 of 0.71 V, which was 70 mV higher than Ru/C, while 120 mV lower than commercial Pt/C, implying a comparable ORR activity to the microwave-synthesized Ru 85 Se 15 /C as previously reported. , In KOH solutions, the ORR activities of Ru/C and RuSe 2 /C catalysts were apparently enhanced (Figure b), similar to previous observations on other Ru-based catalysts. , The best ORR activity in alkaline solution was achieved with RuSe 2 /C (Se/Ru = 2.5), showing the largest E 1/2 of 0.77 V, which was only 90 mV lower than commercial Pt/C. The corresponding Koutecky–Levich plots at 0.40 V are presented in Figure S2, and the electron transfer number ( n ) evaluated from the slopes is supplied in Table .…”
Section: Resultssupporting
confidence: 89%
“…Our previous study revealed that the orthorhombic RuTe 2 /C prepared via a simple microwave route followed by heat treatment at 350 °C exhibited excellent stability and methanol tolerance in both acid and alkaline solutions . In the H 2 /O 2 fuel cell using a Ru loading of 0.26 mg·cm –2 , the P max of 269 mW·cm –2 could be attained with no apparent decay after the durability test at 400 mA·cm –2 for 55 h. This work was extended to synthesize cubic RuSe 2 /C using a similar method in order to improve its stability and maintain its activity in fuel cell performance.…”
Section: Introductionmentioning
confidence: 93%
“…The high catalytic stability was also reported for this kind RuTe 2 /C as oxygen reduction reaction catalysts in both acidic and alkaline media. [27] Faradaic efficiency was also probed (Figure 4b). The amount of hydrogen generated during the electrolysis was recorded and compared with the theoret-ical amount of hydrogen generation for one hour, it was found that the amount of hydrogen gas matched well for these two lines, indicating a Faradic efficiency of nearly 100% for RuTe 2 /Gr in the acidic media.…”
Section: Resultsmentioning
confidence: 99%